K probleme psichiceskoj ustanovki tennisistov - Poljakova, E. P. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The author analyzed and generalized all available theoretical sources, statements, supervision and practical experience of great athletes, and also the long-term competitive experience revealed the following adequate competitive situation, the universal formula of purpose for tennis players of any age, class and level of preparedness: "To win every ball". This purpose is a target level of regulation of activity and its contents remain constant, can vary only a degree of its realization. It corresponds to all the requirements, for any competitive situation in tennis.